2014
DOI: 10.1063/1.4863779
|View full text |Cite
|
Sign up to set email alerts
|

N-type doping of Ge by As implantation and excimer laser annealing

Abstract: The diffusion and activation of arsenic implanted into germanium at 40 keV with maximum concentrations below and above the solid solubility (8 x 10(19) cm(-3)) have been studied, both experimentally and theoretically, after excimer laser annealing (lambda = 308 nm) in the melting regime with different laser energy densities and single or multiple pulses. Arsenic is observed to diffuse similarly for different fluences with no out-diffusion and no formation of pile-up at the maximum melt depth. The diffusion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Arsenic has been used as a doping agent in silicon and germanium to produce n‐type semiconductors for several decades, and many studies have been done on this subject. Even quite recently, the doping issues of As impurities in silicon and germanium are still research topics indicating the importance of the SiAs and GeAs systems . The phase diagrams of the silicon–arsenic and germanium–arsenic systems showed two types of compounds, i.e., XAs and XAs 2 (X = Si, Ge) .…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic has been used as a doping agent in silicon and germanium to produce n‐type semiconductors for several decades, and many studies have been done on this subject. Even quite recently, the doping issues of As impurities in silicon and germanium are still research topics indicating the importance of the SiAs and GeAs systems . The phase diagrams of the silicon–arsenic and germanium–arsenic systems showed two types of compounds, i.e., XAs and XAs 2 (X = Si, Ge) .…”
Section: Introductionmentioning
confidence: 99%
“…1), it is evident that the vacancy distribution extends markedly beyond the melt depth in each of the doped samples. This is rather a peculiar observation, as the SIMS profiles 15 show that the As concentration drops abruptly at depths exceeding the melted layer. Various implantation studies on Si and SiC have found the vacancy-type defects well beyond the projected range of the implanted ions, and it has often been suggested to be due to vacancies produced within the projected range diffusing deeper into the sample.…”
mentioning
confidence: 99%
“…For a comprehensive description of the preparation and characterizations of the samples, the reader can refer to Ref. 15. In brief, secondary ion mass spectrometry (SIMS) and spreading resistance profiling revealed As activation no better than 50%, which motivated the present study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17) However, it is difficult to realize such source junctions in Ge p-channel TFETs (p-TFET) because of the low solid solubility limit and high diffusivity of n-type dopants in Ge. [19][20][21] Defect-free source junctions are also needed to suppress trap-assisted tunneling and generation-recombination processes, which increase the leakage current. 18) Ion implantation is a typical method of introducing impurities into semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%